(untitled) (AMJ (Advanced Medical Journal), 2024)
Background and objectives: Urothelial carcinoma of urinary bladder constitutes 90% of bladder cancer cases. Cyclo-oxygenase 2 as an immune-histochemical marker, is not expressed in normal tissues, while it is expressed in some cancers including urothelial carcinoma. The purpose of this study is detecting the frequency of expression of Cyclo-oxygenase 2 in urinary bladder’s urothelial carcinoma in association with certain clinicopathological variables. Methods: A retrospective study was done on seventy-nine cases (fixed with formalin and embedded in paraffin) of urothelial carcinoma which were chosen haphazardly from a private laboratory in Erbil city over two years (between October 2019 to October 2021). In the present study, Cyclo-oxygenase 2 expression was assessed on the urothelial carcinoma slides. Results: Cyclo-oxygenase 2 was positive in 45.6% of the cases. It was positive in 80% of non-papillary tumors, while it was less expressed (40.6%) in papillary tumors, which means that significant correlation was seen between Cyclo-oxygenase 2 positivity and tumor pattern (papillary vs non-papillary) (p = 0.037). In this study, no important association was found between Cyclo-oxygenase 2 expression and other clinicopathologic features like age (p=0.236), gender (p=517), tumor grade (p=0.106), lymphovascular invasion (p=0.696) and T stage (p=0.061). Conclusion: In this study Cyclo-oxygenase 2 was expressed in less than half of our urothelial tumor samples. A strong association was found between Cyclo-oxygenase 2 positivity and tumor pattern (papillary and non-papillary), but no important association was found between Cyclo-oxygenase 2 positivity and other variables such as age, gender, tumor grade, lymphovascular invasion and tumor stage.